Factor Affecting Work Adjustment of Employees: A Case Study of a Private Company - Janpla, Jureewan; Srimuang, Pongpan (Journal of Management Sciences Suratthani Rajabhat University, 2023)
Due to the epidemic situation of the Coronavirus-19 that has caused the adjustment in working in the organization, employees must work with new working styles which differ from the traditional working style. The purposes of this research were to: (1) compare work adjustment classified by personal factors; (2) study factors affecting work adjustment, and; (3) construct an equation to predict work adjustment. The sample size was 102 employees of a private company selected using simple random sampling. A questionnaire was used to collect data. Statistics for data analysis were frequency, percentage, mean, standard deviation, independent sample t-test, F - test and stepwise multiple regression analysis. The research results after analysis revealed that: (1) the employees with different income and period of employment differently affect work adjustment with a statistically significant level of .05; (2) organizational commitment, agreeableness, openness to experience and extraversion affect work adjustment with a statistically significant level of .05. The predictive powers were at 71.20 percent; (3) the predictive equation of raw score was Y = 1.055 + 0.357 (X6) + 0.208 (X4) + 0.138 (X3) + 0.148 (X2). The results of this research can be used as a guideline for formulating management policies to increase work adjustment of employees.